2018
DOI: 10.2185/jrm.2956
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis is a very rare comorbidity of acute ischemic stroke

Abstract: Background: Although acute pancreatitis is listed among the exclusion criteria for the administration of recombinant tissue plasminogen activator according to the Japanese Guideline for the Management of Stroke, the co-occurrence of acute pancreatitis and acute ischemic stroke has not been investigated. The present study aimed to assess the incidence rate of acute pancreatitis in patients with acute ischemic stroke.Methods: This study consecutively enrolled all patients with ischemic stroke admitted to the Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[3] In our previous review of the literature, we found no case report of acute pancreatitis in a retrospective study of 411 patients with acute ischemic stroke, whereas another study reported one cerebral hemorrhage patient with complications of pancreatitis. [4,5] The main differences from previously reported cases include following. First, except for pancreatitis, most of the previously reported patients had a history of leukemia or heavy drinking, but our case only had a history of pancreatitis.…”
mentioning
confidence: 77%
“…[3] In our previous review of the literature, we found no case report of acute pancreatitis in a retrospective study of 411 patients with acute ischemic stroke, whereas another study reported one cerebral hemorrhage patient with complications of pancreatitis. [4,5] The main differences from previously reported cases include following. First, except for pancreatitis, most of the previously reported patients had a history of leukemia or heavy drinking, but our case only had a history of pancreatitis.…”
mentioning
confidence: 77%
“…However, chronic pancreatitis is associated with a 1.24-fold greater incidence of cerebrovascular disease (adjusted HR: 1.27; 95% CI: 1.19-1.36). 113 Bile acids aid in digestion and are produced in the liver and stored in the gallbladder. Charach et al discovered that bile acid excretion was higher among stroke survivors than in nonsurvivors, suggesting that impaired bile acid excretion is an independent risk factor for stroke, likely by preventing cholesterol excretion and contributing to subendothelial deposition.…”
Section: Fecal Incontinencementioning
confidence: 99%
“…However, chronic pancreatitis is associated with a 1.24-fold greater incidence of cerebrovascular disease (adjusted HR: 1.27; 95% CI: 1.19–1.36). 113…”
Section: Known Gastrointestinal Complications Secondary To Acute Isch...mentioning
confidence: 99%
“…However, very severe and extremely high triglyceride levels may not further increase the risk of stroke ( 4 ). It has been mentioned that the co-occurrence of stroke and acute pancreatitis due to hypertriglyceridemia is rare ( 5 ). This article detailed such a rare case and searched for similar case reports.…”
Section: Introductionmentioning
confidence: 99%